Cloud workflow scheduling algorithm based on multi-objective hybrid particle swarm optimisation. (24th September 2021) - Dai, Gang; Xu, Baomin; Peng, Jianfeng; Zhang, Lei
Particle swarm optimisation has been widely used in solving scheduling problems. This paper proposes a hybrid algorithm namely Hill Climbing with Multi-objective Particle Swarm Optimisation called HCMOPSO, which is based on heuristic local search and multi-objective particle swarm optimisation algorithm. HCMOPSO introduces hill climbing optimisation techniques into particle swarm optimisation algorithm to improve the local search ability. Experimental results show that the HCMOPSO is an effective cloud workflow scheduling algorithm, which has faster convergence velocity and better optimisation ability.